E-011 Merci retrievers as access adjuncts for reperfusion catheters: the grappling hook technique. (12th July 2011) - Hui, F; Hussain, M; Spiotta, A; Bhalla, T; Toth, G; Moskowitz, S; Elgabaly, M; Sivapatham, T; Jafari, N; Rasmussen, P
Abstract : Objective and Importance: Expeditious and stable access in the setting of acute ischemic stroke is foundational to mechanical revascularization of large vessel occlusions of the cerebral vasculature, particular when using an aspiration based system. Proximal vascular tortuousity and unfavorable anatomic variability may impede vascular access necessary for revascularization. In particular, the ophthalmic segment often proves difficult for large caliber aspiration catheters to navigate. We describe an approach using the Merci Retriever system as an adjunct to gain stable catheter access for aspiration. Clinical Presentations: Three patients presenting with acute ischemic stroke were treated via mechanical thrombectomy using the Penumbra 054 system. However, due to anatomical configurations, access to the M1 segment was challenging, with difficulty traversing the ophthalmic segment of the internal carotid artery ipsilateral to the respective M1 segment occlusion. Intervention: Aspiration catheter access into the distal middle cerebral artery was achieved via advancement of an 18L microcatheter followed by deployment of an appropriately sized Merci Retriever into the M1 segment. Gentle tension on the Retriever was applied, altering the angle at which the Aspiration catheter navigated the ophthalmic segment, affording accelerated access past the ophthalmic artery origin and into the ipsilateral M1 segment and clot. Retraction of the retriever into the 18L was followed by removal of the 18L in each case, which was in turn followed by aspiration using the Penumbra Aspiration catheter. Conclusion: Time is of the essence in treating acute ischemic stroke, and, upon occasion, tortuous proximal anatomy may impede access to the occluded vessel. By making use of the apposition of a Merci retriever against the wall of a vessel, increased tension and straightening along the core wire changes the angle at which the large profile catheter makes with the vessel. As such, in unfavorable ophthalmic segment anatomy, this technique may be employed to advance an aspiration catheter to treat the offending embolus in the setting of an acute ischemic stroke.